MAIN PROBLEMS OF GRAIN PRODUCTION IN YAKUTIYA - S. S. Sleptsov; М. S. Samsonova (Зерновое хозяйство России)
The article has presented the data about the history of agriculture in Yakutiya; it has shown the dynamics of cultivated areas growth before the Great Patriotic War; it has given the information about the amount of the breeding work fulfilled in the mentioned period by the researchers of the Yakutsk state breeding station. The article has established direct and indirect reasons of decrease in that branch of plant-growing, which started in the 50s of the previous century and are continued till present days. The authors have suggested the methods of productivity increase of grain crops, based on intensification of production, stronger focus on the problems of plant protection. The article has presented the data on harmfulness of leaf diseases, Oscinella frit, Oscinella pusilla and different weeds. Efficiency of protective measures in production has been shown in the article. The necessity of rational use of nature resources, strengthening of the material-technical base, implementation of the achievements of science-technical progress with participation of scientists and use of adaptive intensification have been considered in the paper.